PENGARUH KOMPENSASI LANGSUNG DAN KOMPENSASI TAK LANGSUNG TERHADAP KINERJA KARYAWAN PADA PT. CAHAYA SURYA JAYA SENTOSA AREA MADURA - Gazali Gazali; Adriani Kusuma; Muslimatul Aina (Al-Amien Prenduan for Islamic Institute, 2022)
This research aims to determine direct compensation and indirect compensation on employee performance at PT. Surya Jaya Sentosa Light. In addition, this study aims to determine the most dominant variables in influencing employee performance. Research conducted at PT. CAHAYA Surya Jaya is a type of associative or relationship research. The types of data used are qualitative and quantitative data. Sources of data used are primary data and secondary data. Research variables consist of independent variables and dependent variables. The independent variable consists of direct compensation (X1) and indirect compensation (X2) and the dependent variable consists of employee performance (Y2). Hypothesis testing using F test and t test using statistical-based data processing, namely SPSS 20. The results showed that there was a simultaneous influence between direct compensation and indirect compensation on the performance of employees of PT. Surya Jaya Sentosa Light. Meanwhile, the more dominant variable is the direct compensation variable.Â